Pseudocapacitive Characteristics of Low-Carbon Silicon Oxycarbide for Lithium-Ion Capacitors - Halim, Martin; Liu, Guicheng; Ardhi, Ryanda Enggar Anugrah; Hudaya, Chairul; Wijaya, Ongky; Lee, Sang-Hyup; Kim, A-Young; Lee, Joong Kee (American Chemical Society, 2017)
Lithium-ion capacitors (LICs) and lithium-ion batteries (LIBs) are important energy storage devices. As a material with good mechanical, thermal, and chemical properties, low-carbon silicon oxycarbide (LC-SiOC), a kind of silicone oil-derived SiOC, is of interest as an anode material, and we have examined the electrochemical behavior of LC-SiOC in LIB and LIC devices. We found that the lithium storage mechanism in LC-SiOC, prepared by pyrolysis of phenyl-rich silicon oil, depends on an oxygen-driven rather than a carbon-driven mechanism within our experimental scope. An investigation of the electrochemical performance of LC-SiOC in half- and full-cell LIBs revealed that LC-SiOC might not be suitable for full-cell LIBs because it has a lower capacity (238 mAh g(-1)) than that of graphite (290 mAh g(-1)) in a cutoff voltage range of 0-1 V versus Li/Li+, as well as a substantial irreversible capacity. Surprisingly, LC-SiOC acts as a pseudocapacitive material when it is tested in a half-cell configuration within a narrow cutoff voltage range of 0-1 V versus Li/Li+. Further investigation of a "hybrid" supercapacitor, also known as an LIC, in which LC-SiOC is coupled with an activated carbon electrode, demonstrated that a power density of 156 000 W kg(-1) could be achieved while maintaining an energy density of 25 Wh kg(-1). In addition, the resulting capacitor had an excellent cycle life, holding similar to 90% of its energy density even after 75 000 cycles. Thus, LC-SiOC is a promising active material for LICs in applications such as heavy-duty electric vehicles.
Keywords: ENERGY-STORAGE DEVICE; RICH SIOC ANODES; CATHODE MATERIAL; GRAPHITE ANODE; LONG-CYCLE; LI; SUPERCAPACITOR; BATTERY; ELECTRODES; PARTICLES